Career Guidance: Challenges for the New Century under an International Perspective - Jenschke, Bernhard (2005)
This paper is dedicated to key issues of the actual challenges in all societies regardless their developmental level and how the international guidance community is coping with these challenges. It deals with the importance of guidance in a changing society, quality assurance, access to services and qualification of guidance practitioners under an international perspective.